Analisis daya dukung air tanah dengan metode statis di bentang lahan pesisir Kapanewon Temon, Kabupaten Kulon Progo - Wati, Diah Retno; Adji, Tjahyo Nugroho; Rahardjo, Noorhadi (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2024)
In order to keep the ecosystem's water resources in balance and prevent a decline in their availability, wise use of clean water is essential. In particular, since groundwater is one of the sources of clean water, this needs to be done. Kapanewon Temon which is located on a coastal stretch that currently has a new airport, namely Yogyakarta International Airport (YIA), which has the potential to increase the need for clean water. This study aims to determine the status of groundwater carrying capacity in Kapanewon Temon, Kabupaten Kulon Progo. The method used in this research is a survey method with primary data supported by secondary data on various study objects regarding groundwater for clean water needs.The survey results were then analyzed descriptively qualitatively and quantitatively. In this case, the status of the carrying capacity of the Kapanewon Temon coastal ecosystem is in the safe category.